MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MTS DENGAN MENGGUNAKAN PROBLEM POSING - Elza Efriyani Nursyifaa; Eka Senjayawati (IKIP Siliwangi, 2018)
The purpose of this research is to assess whether the improvement of students' mathematical problem solving skills using Problem Posing approach is better than those using ordinary learning. The population in this research is MTs Nurul Falah Cimahi. This research instrument in the form of a test of mathematical problem solving skills of five items. This research data is processed using software SPSS Version 22. Data analysis used is test of normality and test of two difference of mean. The result of this research stated that the achievement and improvement of problem solving skills of MTs students using Problem Posing approach is better than the normal learning, and the implementation using Problem Posing approach has been run in accordance with the learning procedure found and the difficulties experienced by students in solving the problem of solving skills mathematical problems are present in indicators of understanding problems, planning problems, implementing problem-solving plans, and re-examination.